INTEGRATED SIMULATION AND EFFICIENCY ANALYSIS OF ASP FLOODING USING CMG-STARS FOR ENHANCED OIL RECOVERY IN THE KASHAGAN OIL FIELD - Sherdebayev, Rustem (Nazarbayev University School of Mining and Geosciences, 2025)
Alkali-Surfactant-Polymer (ASP) flooding for enhanced oil recovery (EOR) at the Kashagan oil field, one of Kazakhstan's most technically difficult reservoirs, is thoroughly evaluated using simulation in this thesis. Conventional recovery techniques are still mostly ineffectual in the presence of high hydrogen sulfide gas concentration, high formation water salinity (>180,000 ppm), and high reservoir temperatures (~99°C). However, by lowering interfacial tension, increasing mobility ratio, and changing wettability, ASP flooding has the potential to get beyond these restrictions. The study simulates ASP flooding performance under different salinity levels, chemical concentrations, and well placement patterns using the CMG-STARS simulator. It was chosen to apply cartesian grid system with dimensions of 15*15*7 blocks for heterogeneous, anisotropic reservoir model. Rock properties were used as general values for carbonate reservoirs, while fluid properties were used for Kashagan oil sample. Initial conditions for pressure, temperature, and saturation are based on average reservoir characteristics from the literature review. The main well placement scenario was chosen to be normal 5-spot patter, while the sensitivity analysis also considers middle 5-spot, normal 7-spot, and middle 7-spot well placements. Alkali-surfactant (AS), polymer-only, and complete ASP flooding strategies were all compared in simulations based on the cumulative oil production results. The findings showed that ASP flooding outperformed AS and polymer flooding alone, with the largest cumulative oil recovery (~360,000 bbl) and the lowest water-oil ratio (~11). Additional sensitivity analysis showed that optimal well designs (normal 5-spot pattern) and reduced injection salinity greatly improve oil recovery. The best chemical composition, consisting of 0.4 weight percent alkali, 0.1 weight percent surfactant, and 0.075 weight percent polymer, has the maximum economic return with a pseudo-NPV of $27.2 million, according to the thesis, which also includes pseudoeconomic analysis. For high-salinity, carbonate reservoirs like Kashagan, the results indicate that ASP flooding is both technically feasible and economically beneficial with the right optimization, despite operational obstacles such chemical degradation and adsorption.
Комплексное моделирование и анализ эффективности заводнения ASP с использованием CMG-STARS для повышения нефтеотдачи на нефтяном месторождении Кашаган
Қашаған кен орнында мұнайды жоғарылату үшін CMG-STARS көмегімен ASP су тасқынының кешенді модельдеу және тиімділік талдауы
Keywords: ASP flooding; Kashagan oil field; CMG modeling; PQDT_Master